Asymmetry in the Permanent Price Impact of Block Purchases and Sales: Theory and Empirical Evidence. Issue 4 (9th November 2016) - Frino, Alex; Mollica, Vito; Romano, Maria Grazia; Zhou, Zeyang
Abstract : Previous research has identified that the information effects of buyer‐initiated trades are greater than seller‐initiated trades. We develop a theoretical model that predicts block purchases are relatively more informed in bear markets and block sales are relatively more informed in bull markets. Using a sample of large trades executed in the E‐mini S&P 500 index futures and SPDR S&P 500 exchange traded fund, we find evidence consistent with our theoretical model. Our results are robust to volatility and macro‐economic news announcements categorized as bullish or bearish. © 2016 Wiley Periodicals, Inc. Jrl Fut Mark 37:359–373, 2017